Clinical and pathogenetic differences of the course of flow nonalcoholic steatohepatitis in obese patients with and without hypertension - O.S. Khukhlina; O.E. Mandryk; A.A. Antoniv (Zaporozhye State Medical University, 2013)
The article is devoted to the study of clinical and pathogenetic peculiarities of nonalcoholic steatohepatitis, a condition of components of connective tissue, metabolic intoxication, hemostasis and fi brinolysis by comorbidity with and without stage II hypertension. It was found that in the course of comorbid nonalcoholic steatohepatitis with hypertension and obesity compared with nonalcoholic steatohepatitis without hypertension there is a higher intensity of hemostasiological disorders.